Intervallbeobachter für lineare parametervariante Systeme und deren Anwendung auf die Asynchronmaschine - Krebs, Stefan (Karlsruher Beiträge zur Regelungs- und Steuerungstechnik / Karlsruher Institut für Technologie, Institut für Regelungs- und Steuerungssysteme, 2018)
The topic of this publication is the design of two new set-based methods for the determination of the states of linear parameter-varying systems. These sets are computed by interval observers based on unknown but bounded inputs, outputs and parameters. The effectiveness of the methods is demonstrated by the state estimation of an induction motor that is achieved by combining the interval observers with a novel model of a voltage source inverter.